Channel capacity optimization scheme for safety applications in vehicular ad hoc networks. (6th July 2022) - Sharma, Swati; Chahal, Manisha; Harit, Sandeep; Kumar, Neeraj
Summary: Vehicular ad hoc networks (VANETs) have attracted significant attention due to their safety, traffic management, and infotainment applications. However, vehicular communication suffers from network congestion caused by high vehicle density, which raises numerous challenges for efficiently disseminating emergency messages in vehicular safety applications. This paper aims to solve the problem of capacity optimization of the control channel (CCH) during the delivery of emergency messages. Hence, we propose a novel channel capacity optimization scheme for safety application (CCOSSA). The performance of the CCOSSA scheme is evaluated by performing comprehensive traffic and network simulations regarding various parameters such as the probability of reception, channel busy time (CBT) ratio, and average delay. CCOSSA scheme is compared with the state‐of‐the‐art schemes under varying vehicle density and distance from the source in which the proposed scheme shows an improvement in the performance. Abstract : In this article, we propose a solution that varies the transmission power of the beacon messages according to the measured Channel Monitoring Vector (CMV). We have taken into account the interference between different transmission beams disseminated by the source vehicle directed toward vehicles in the communication range of the source vehicle. The proposed scheme channel capacity optimization scheme for safety application (CCOSSA) is evaluated by considering different network parameters and several performance metrics. The result represents an improvement in the CCOSSA scheme's performance compared to similar schemes.